Γ-convergence and homogenisation for a class of degenerate functionals. (January 2020) - Dirr, Nicolas; Dragoni, Federica; Mannucci, Paola; Marchi, Claudio
Abstract: This paper is on Γ -convergence for degenerate integral functionals related to homogenisation problems in the Heisenberg group. Here both the rescaling and the notion of invariance or periodicity are chosen in a way motivated by the geometry of the Heisenberg group. Without using special geometric features, these functionals would be neither coercive nor periodic, so classic results do not apply. All the results apply to the more general case of Carnot groups.